2020
DOI: 10.1186/s12920-020-0701-6
|View full text |Cite
|
Sign up to set email alerts
|

A de novo 2.2 Mb recurrent 17q23.1q23.2 deletion unmasks novel putative regulatory non-coding SNVs associated with lethal lung hypoplasia and pulmonary hypertension: a case report

Abstract: Background: Application of whole genome sequencing (WGS) enables identification of non-coding variants that play a phenotype-modifying role and are undetectable by exome sequencing. Recently, non-coding regulatory single nucleotide variants (SNVs) have been reported in patients with lethal lung developmental disorders (LLDDs) or congenital scoliosis with recurrent copy-number variant (CNV) deletions at 17q23.1q23.2 or 16p11.2, respectively. Case presentation: Here, we report a deceased newborn with pulmonary h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…The increase of SHH pathway expression in ACDMPV could represent a compensatory response to the loss of FOXF1. In addition to FOXF1, SHH is thought to control expression of the TBX genes, which are also associated with LLDD and PAH in humans [64][65][66][67][68][69] and are known regulators of lung branching in mice [70,71]. Of note, in our recent ChIP-seq study performed in IMR-90 fetal lung fibroblasts, we demonstrated that TBX2 and/ or TBX4 bind to FOXF1, FENDRR, their promoter(s) and lung-specific enhancer, as well as to genes from the axon guidance/SEMA signaling (SEMAs, PLXNs, and NRP), that were found to be deregulated in ACDMPV patients in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The increase of SHH pathway expression in ACDMPV could represent a compensatory response to the loss of FOXF1. In addition to FOXF1, SHH is thought to control expression of the TBX genes, which are also associated with LLDD and PAH in humans [64][65][66][67][68][69] and are known regulators of lung branching in mice [70,71]. Of note, in our recent ChIP-seq study performed in IMR-90 fetal lung fibroblasts, we demonstrated that TBX2 and/ or TBX4 bind to FOXF1, FENDRR, their promoter(s) and lung-specific enhancer, as well as to genes from the axon guidance/SEMA signaling (SEMAs, PLXNs, and NRP), that were found to be deregulated in ACDMPV patients in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In the studies of Karolak J.A. et al, a complex inheritance of lethal developmental disorders of the lungs due to disruption of the TBX-FGF pathway has been described [ 86 ]. The emergence of rare coding variants involving FGF10 with putative hypomorphic noncoding SNVs implies a complex inheritance of pulmonary hypoplasias.…”
Section: Resultsmentioning
confidence: 99%
“…Infants with LLDD who had a pathogenic TBX4 or FGF10 variant also had at least one noncoding rare SNV within the predicted lung-specific enhancer located upstream to TBX4. We hypothesized that those noncoding variants decreased the activity of the enhancer causing in trans reduction of TBX4 or FGF10 expression and resulting in LLDD (Karolak et al, 2020(Karolak et al, , 2019. Moreover, TBX4 pLI score of 0.5 indicates that a deleterious variant alone might not be sufficient to cause a disease and the variability in the phenotype can be explained by the contribution of the other variants in the regulatory elements (Table S1).…”
Section: Discussionmentioning
confidence: 99%